Electronic patient records and teleophthalmology. Part 2: concrete projects in ophthalmology - Schargus, M.; Michelson, Georg; Grehn, F. (Ophthalmologe, 2011)
Electronic storage of patient-related data will replace paper-based patient records in the near future. Because of the high visualization needed in ophthalmology integrated electronic data storage and usage will be very useful. Chronic diseases like glaucoma, macular degeneration and diabetic retinopathy would benefit from long-term data storage and analysis. Unfortunately there are nearly no widely accepted systems available providing these options. Another important point is the simplification of existing diagnostic procedures and nomenclature on an international level. Increasing mobility of patients requires a better portability of existing medical examination data between different physicians. This is the only way to provide continuously high levels of quality in patient care and to simultaneously reduce costs and prevent unnecessary secondary examinations.
EVALuna2:21061